1999
DOI: 10.1074/jbc.274.5.2866
|View full text |Cite
|
Sign up to set email alerts
|

Selenoprotein P in Human Plasma as an Extracellular Phospholipid Hydroperoxide Glutathione Peroxidase

Abstract: Selenoprotein P is an extracellular protein containing presumably 10 selenocysteines that are encoded by the UGA stop codon in the open reading frame of the mRNA. The function of selenoprotein P is currently unknown, although several indirect lines of evidence suggest that selenoprotein P is a free radical scavenger. We first developed a conventional procedure to isolate selenoprotein P from human plasma. Next, we investigated the reactivities of selenoprotein P against various hydroperoxides in the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
192
2
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 251 publications
(198 citation statements)
references
References 41 publications
2
192
2
2
Order By: Relevance
“…28 Selenoprotein P concentrations in plasma are known to be a useful marker of selenium status though neither circulating nor tissue concentrations of selenoprotein P have been measured in human pregnancy. In a UK study, selenoprotein P and plasma GPx together were found to account for up to 90% of total plasma selenium (cited in reference 26).…”
Section: Commentmentioning
confidence: 99%
“…28 Selenoprotein P concentrations in plasma are known to be a useful marker of selenium status though neither circulating nor tissue concentrations of selenoprotein P have been measured in human pregnancy. In a UK study, selenoprotein P and plasma GPx together were found to account for up to 90% of total plasma selenium (cited in reference 26).…”
Section: Commentmentioning
confidence: 99%
“…These enzyme families share the GSH binding thioredoxin domain, but are otherwise structurally and mechanistically dissimilar. In particular, GPxs contain a selenocysteine, which reacts covalently with GSH, generally via a ping-pong enzyme reaction mechanism [50]. In contrast, GSTs use a conserved tyrosine, serine or cysteine residue to interact with the thiol group of GSH, thus increasing the reactivity of GSH, typically via a sequential mechanism [51][52][53].…”
Section: Ure2 As a Glutathione Transferasementioning
confidence: 99%
“…Human Aβ and Aβ were purchased from Peptide Institute Inc. (Osaka, Japan); Aβ 1-28 , 1-palmitoyl-2-(13-hydroperoxy-cis-9, trans-11-octadecadienoyl) phosphatidylcholine (PLPC-OOH) was prepared from PLPC as described previously (18,32,33). Other chemicals were of the highest quality commercially available.…”
Section: Methodsmentioning
confidence: 99%